MATH SOLVE

4 months ago

Q:
# 30 points. Help pleaseConsider this system of equations:2x + 1/4y = 3 ( equation A )2/3x - y = 6 ( equation B )The expressions that give the value of y are a) A - 3Bb) A - (3B/2)c) 2A - 3Bd) (A/3) + B)anda) A + 3Bb) A+ (3B/2)c) (A/3) - Bd) (A/3) - 2BThe solution for the given system is a) (27/13, 60/13)b) (-27/13, 60/13)c) (27/13, -60/13)d) (-27/13, -60/13)

Accepted Solution

A:

A - 3B and (A/3) - B

solving :-

2x + 1/4 y = 3

2/3x - y = 6 Multiply this by 3

2x - 3y = 18 subtract this from first equation

0 + 13/4y = -15

y = -60/13

x = (3 - 1/4*-60/13) / 2 = 27/13

Thats C

solving :-

2x + 1/4 y = 3

2/3x - y = 6 Multiply this by 3

2x - 3y = 18 subtract this from first equation

0 + 13/4y = -15

y = -60/13

x = (3 - 1/4*-60/13) / 2 = 27/13

Thats C